Cote d'Ivoire : Seventh and Eighth Reviews under the Extended Credit Facility Arrangement and the Extended Arrangement under the Extended Fund Facility, Request for Waivers of Nonobservance of Performance Criteria, and Proposal for Post-Program Monitoring-Press Release; Staff Report; and Statement by the Executive Director for Cote d'Ivoire. (IMF Staff Country Reports; Country Report ;, 2020)
Prior to the COVID crisis, Cote d'Ivoire had established a strong track record of economic policies, although domestic revenue mobilization has disappointed. The authorities reacted swiftly to the pandemic, supported by emergency financing from the IMF and other donors. They implemented a health and economic response plan combined with frontloaded capital spending, relaxing the 2020 fiscal stance by 3 1\2 ppt of GDP compared to pre-COVID projections. The authorities will start consolidating the fiscal position in 2021 while supporting the recovery, with tax measures underpinning the 2021 budget. Beyond, the authorities are committed to returning to the regional fiscal deficit norm of 3 percent of GDP by 2023. The October 2020 presidential election was accompanied by socio-political tensions.